The role of pet ownership as a possible buffer variable in traumatic experience - Arambašić, Lidija; Keresteš, Gordana (1998)
Studies have shown that pet's companionship could help people in dealing with stress. Since pets can be regarded as a form of social support, it can be assumed that they can also ameliorate after-effects of traumatic experiences. According to Wilson's model of traumatic stress, social support is a key moderator variable in reducing intensity of traumatic reactions. The aim of this study was to examine whether three groups of children (withouth pet N=173, with dog/cat N=295, with other pets N=144) differ in intensity of posttraumatic stress reactions (PTSR) and ways of coping with stress. Participants in the study were primary school children from Slavonia, one of the Croatian regions heavily affected by the war. The Questionnaire for measuring PTSR and the Ways of children's coping scale were administered on 612 students. In ANOVA for PTSR one two-way interaction was statistically significant (pet ownership x gender) showing that girls with pets other than dog/cat have the highest level of PTSR. Boys withouth pets and girls with dog/cat have the least PTSR. Separate ANOVAs were computed for four coping strategies. Following statistically significant F-ratios were obtained: expressing emotions - gender, pet ownership and age ; seeking social support - gender, pet ownership and age ; problem solving - gender and interaction between pet ownership and age ; avoidance - age. Comparing three groups of children, results show that students with dog/cat use more often than other groups expressing emotions, seeking social support and problem solving. From obtained results it seems that children with dog/cat have more differentiated coping strategies what may be helpful in reducing PTSR, specially in the case of girls owning dog/cat who have the least PTSR.
Projekt MZOS
ENG